OBSERVATIONS ON THE SPAWNING SEASON AND THE FISHERIES OF THE SPOTTED SEER. SCOMBEROMORUS GUTTATUS (BLOCH & SCHNEIDER) - Krishnamoorthi, B. (Indian Journal of Fisheries, 2016)
The spotted seer or Scomberomorus guttatus, is an important and much esteemed table fish, standing next in importance to Leiognathus splendens in the fishery of Rameswaram Island, where approximately 320 tons of this fish, fetching a market price of about Rs. 250,000, are landed every year (Krishnamoorthi, 1958). It is well known in the fishery of all coastal areas of India. Nevertheless the available literature furnishes Uttle exact information about its biology except for some remarks on taxonomy and geographical distribution by Day (1889) and Weber and Beaufort (1951), a description of the egg by Delsman (1931) and notes on life-history and feeding habits by Vijayaraghavan (1955). Accordingly, the present study was initiated to gather some knowledge of the biology of this important commercial species.